2009
DOI: 10.1080/09735070.2009.11886333
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-medicinal Plants Used to Cure Different Diseases by Tribals of Mayurbhanj District of North Orissa

Abstract: Mayurbhanj, a hilly district, is rich in ethno medicinal plants. In the present paper 58 plant species belonging to 34 families used in folk medicine have been documented. Due to poor condition of modern healthcare facilities and poverty, indigenous people of the district fully or partially depend on local medicinal plants. An attempt has been made to document traditional knowledge from the baidyas group of Hatikote, Moroda & Rasgovindpur and Udala & Kaptipada blocks of Mayurbhanj district on the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 5 publications
(4 reference statements)
2
19
0
Order By: Relevance
“…Data was compared with the available previous literature and found that many of the usages listed are not recorded earlier [9]. Earlier there were no reports on mouth ulcers from the present study area.…”
Section: Discussionmentioning
confidence: 99%
“…Data was compared with the available previous literature and found that many of the usages listed are not recorded earlier [9]. Earlier there were no reports on mouth ulcers from the present study area.…”
Section: Discussionmentioning
confidence: 99%
“…In Mayurbhanj district of Orrisa, 58 plant species belonging to 34 families used in folk medicine have been documented (Rout et al 2009). Due to poverty and the poor conditions of modern healthcare facilities, indigenous people of Orrisa fully or partially depend on local medicinal plants.…”
Section: Ethnomedicinal Plants Of Northern Indiamentioning
confidence: 99%
“…The plates were incubated at 37 o C for 24hrs for bacteria and 30 o C for 48hrs for fungi. The negative control used was DMSO [20] for both fungi and bacteria and 50µg/ml for Nystatin. After specified time of incubation, the plates were brought out of incubator and the diameter of zone of inhibition was measured with ruler calibrated in millimeters.…”
Section: Antimicrobial Screeningsmentioning
confidence: 99%